(untitled) (International Journal of Food and Nutritional Sciences, 2022)
At the end of the supply chain, the Aim of Research has pointed to the ethical behavior aspect of decisions that lead to food waste. The present study reviews the literature on food wastage to reveal the role of ethical behavior among consumers in controlling, reducing, and preventing food waste. Analysis methodology The research is literature-driven and aims to expose the ethical consumer conduct that underlies the behaviors that contribute to food waste. To deliver unconventional research ideas that underline the interplay of these factors, it uses previous studies in the fields of responsible consumerism, food wastage, pro-environmental actions, and sustainability. Based on the literature, the paradoxical existence of the predicted effect of ethical conduct was considered and verified. The results indicate that the expectation of ethical conduct due to desires to be remembered as a good provider or to show one’s love can lead to acts that contribute to reduced waste while anticipating a lack of ethical conduct can generate a negative result concerning food waste.